Use of a quantitative data report in a hypothetical decision scenario for health policymaking: a computer-assisted laboratory study - Wronski, Pamela; Wensing, Michel; Ghosh, Sucheta; Gärttner, Lukas; Müller, Wolfgang; Koetsenruijter, Jan (BMC medical informatics and decision making, 2021)
Quantitative data reports are widely produced to inform health policy decisions. Policymakers are expected to critically assess provided information in order to incorporate the best available evidence into the decision-making process. Many other factors are known to influence this process, but little is known about how quantitative data reports are actually read. We explored the reading behavior of (future) health policy decision-makers, using innovative methods.
Gesehen am 26.03.2021